Desert war the North African campaign, 1940-1943 - Moorehead, Alan 1910- (Penguin Books, 2001)
North Africa was the site of some of the most volatile battles of World War II. For journalist Alan Moorehead, it was war in its purest form, "a knight's tournament in empty space."" "In Desert War, which includes the complete texts of The Mediterranean Front, A Year of Battle, and The End of Africa, Moorehead writes about what he saw. He recounts with dazzling prose and intimate detail the heroes and legends, the soldiers and prisoners, the military strategies, the strengths and weaknesses of those involved, and portraits of generals Rommel, Montgomery, and Patton. Woven throughout are observations on the landscape, the Mediterranean shores and the vast desert, which inevitably played a role in shaping the battles. For Moorehead, "desert warfare resembled war at sea. Men moved by compass. No position was static. Each truck or tank was as individual as a destroyer."" "Written by a man who lived and breathed the conflict in North Africa during World War II, Desert War is a eyewitness account and an inspired piece of writing by a master of his craft.